THE RELATIONSHIP BETWEEN NUMERICAL ABILITY, PARENTAL CONCERN, AND LEARNING MOTIVATION WITH MATHEMATICS LEARNING OUTCOMES IN STUDENTS CLASS VII OF SMP - Nely Ulfatullatifah; Aris Thobirin (Universitas Ahmad Dahlan, 2018)
This research is motivated by students' numerical abilities, which are getting low, parental concern, and learning motivation. The purpose of this research was to know that there is a positive connection that significant or not numerical ability, parental concern, and the learning motivation to mathematics learning outcomes in students class VII of SMP Muhammadiyah 9 Yogyakarta Second Semester Year of Academic 2016/2017. This research is classified as quantitative research with the population entire in students class VII of SMP Muhammadiyah 9 Yogyakarta Second Semester Year of Academic 2016/2017 consisting of 5 classes as many as 161 students. The sample was taken by a random sampling technique to the class and obtained class VII A of 32 students sample. Data collection techniques used tests and questionnaires. Data analysis used multiple linear regression and correlation analysis. The results showed there is a positive and significant relationship among numerical ability, parental concern, and learning motivation the results of learning mathematics with dan so that obtained with = 0,522432068 and 91,97803087 + 0,24612655 + 0,647302764 + 0,85573043 as well as Relative Contribution 17,274%, RC 42,307%, RC 40,419%, Effective Contribution(EC) 9,025%,EC 22,102%, 21,116%.